2011
DOI: 10.1038/emboj.2011.386
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide-induced calcium release via ryanodine receptors regulates neuronal function

Abstract: Mobilization of intracellular Ca 2 þ stores regulates a multitude of cellular functions, but the role of intracellular Ca 2 þ release via the ryanodine receptor (RyR) in the brain remains incompletely understood. We found that nitric oxide (NO) directly activates RyRs, which induce Ca 2 þ release from intracellular stores of central neurons, and thereby promote prolonged Ca 2 þ signalling in the brain. Reversible S-nitrosylation of type 1 RyR (RyR1) triggers this Ca 2 þ release. NO-induced Ca 2 þ release (NICR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(108 citation statements)
references
References 63 publications
3
104
0
1
Order By: Relevance
“…In conclusion, in combination with the observations in our previous study, 15 it is suggested that NICR is dependent on the NO-dependent S-nitrosylation of RyR1 rather than on indirect actions of peroxynitrite or cyclic GMP (Fig. 3).…”
supporting
confidence: 60%
See 2 more Smart Citations
“…In conclusion, in combination with the observations in our previous study, 15 it is suggested that NICR is dependent on the NO-dependent S-nitrosylation of RyR1 rather than on indirect actions of peroxynitrite or cyclic GMP (Fig. 3).…”
supporting
confidence: 60%
“…However, it was resistant to an intracellular application of 10 mM ascorbic acid, which completely abolishes BS-induced NICR. 15 Therefore, the peroxynitrite-dependent digitized at 20 kHz. After obtaining a stable initial recording for at least 10 min, 60 burst stimulations (1 burst stimulation: 5 pulses at 50 Hz) were repeatedly applied at 1 Hz to induce LTP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ayrica RyR soma ve dendritlerde, aksonlarda, pre-ve post-sinaptik terminallerde yer almaktadir [8,9]. Purkinje hücrelerinin dendritlerinde de çok miktarda RyR1 eksprese edilir [12].…”
Section: Santral Sinir Sistemindeki Ryanodin Reseptörleriunclassified
“…Moreover, maximal activation can be attained at lower concentrations of ATP for oxidized RyR channels [21] . Alternatively, Kakizawa [22] recently showed that nitric oxide (NO) can induce RyR1 activation through S-nitrosylation at a specific cysteine residue (C3635) and evoke Ca 2+ release from the ER. Using cultured neurons derived from RyR1 -/-mice, in which NO-induced Ca 2+ release is absent, they demonstrated that NO-induced neuronal cell death was reduced.…”
Section: Ryanodine Receptor Channels (Ryrs)mentioning
confidence: 99%